Ovarian Carcinoma in a Young Pregnant Woman - Singh, Jitendra Kumar; Dangal, Ganesh; Karki, Aruna; Pradhan, Heema Kumari; Shrestha, Ranjana; Bhattachan, Kabin; Paudel, Rekha; Bajracharya, Nishma; Tiwari, Kenusha Devi; Bharati, Sonu (Journal of Nepal Health Research Council, 2021)
Ovarian cancer during pregnancy is a rare event. Little is known about the treatment of this condition due to the lack of randomized trials and cohort studies. A case of 28 years female, from Kathmandu, visited Out-Patients Department with complaint of amenorrhea for 8 weeks associated with nausea and occasional pain abdomen. Dating scan was done which showed a single live intrauterine pregnancy corresponding to 8 weeks 4 days of gestation with incidental finding of adnexal cysts in both adnexa, measuring 3.6 x 3.6 cm on right and on left 3.2 x 3.6 cm. The cysts did not show any septations. At 38 weeks, she underwent caesarean section and delivered a healthy baby girl. Intra-operatively, bilateral ovarian cysts were identified, both 2x2 cm simple-looking cysts. Enucleation of bilateral ovarian cysts was done. The specimen was sent for histopathology which showed serous carcinoma of low grade in bilateral ovaries. Staging surgery was then carried out after 6 weeks. Histopathology report showed serous carcinoma of low grade in both ovaries. We present here the case of ovarian cancer during pregnancy. Keywords: Ovarian cancer; pregnancy